Analisis Kebijakan dan Mutu Pendidikan Islam di Sekolah Dasar - Abdul Muluk; Ahmad Sulhan (Universitas Muhammadiyah Mataram, 2025)
Abstract: This study aims to analyze the development of Islamic education policies and their impact on the quality of education in elementary schools through a Systematic Literature Review (SLR) approach. The literature sources were obtained from Scopus, DOAJ, and Google Scholar databases, limited to publications from the last ten years. The selection process followed the stages of identification, screening, eligibility, and inclusion, resulting in a collection of articles relevant to the research focus. The findings indicate that Islamic education policies have a significant influence on improving the quality of primary education, particularly through three key dimensions: strategic management, curriculum development, and community engagement. In terms of management, policies grounded in Islamic values strengthen institutional vision, governance effectiveness, and school leadership. Within the curriculum dimension, the integration of spiritual, moral, and general knowledge components fosters a more holistic and adaptive learning model aligned with contemporary educational demands. Meanwhile, community involvement and stakeholder participation play an essential role in ensuring the sustainability and effectiveness of policy implementation. This study concludes that well-designed and responsive Islamic education policies are capable of creating a higher-quality learning ecosystem that is relevant, inclusive, and character-oriented for elementary school students. The findings provide important implications for policymakers, educators, and researchers in optimizing the future direction of Islamic education development.Abstrak: Penelitian ini bertujuan untuk menganalisis perkembangan kebijakan pendidikan Islam dan dampaknya terhadap mutu pendidikan di sekolah dasar melalui pendekatan Systematic Literature Review (SLR). Sumber literatur diperoleh dari database Scopus, DOAJ, dan Google Scholar dengan batasan publikasi sepuluh tahun terakhir. Proses seleksi dilakukan melalui tahapan identifikasi, screening, eligibility, dan inclusion sehingga menghasilkan kumpulan artikel yang relevan dengan fokus penelitian. Hasil kajian menunjukkan bahwa kebijakan pendidikan Islam memiliki pengaruh signifikan terhadap peningkatan kualitas pendidikan dasar, terutama melalui tiga aspek utama, yaitu manajemen strategis, pengembangan kurikulum, dan keterlibatan masyarakat. Dalam aspek manajemen, kebijakan berbasis nilai-nilai Islam mendorong penguatan visi kelembagaan, efektivitas tata kelola, dan kepemimpinan kepala sekolah. Pada dimensi kurikulum, integrasi nilai spiritual, moral, dan pengetahuan umum menghasilkan model pembelajaran yang lebih holistik dan adaptif terhadap perkembangan zaman. Sementara itu, partisipasi masyarakat dan pemangku kepentingan eksternal berperan memperkuat implementasi kebijakan secara berkelanjutan. Penelitian ini menegaskan bahwa kebijakan pendidikan Islam yang dirancang secara komprehensif dan responsif mampu menciptakan ekosistem pembelajaran yang lebih berkualitas, relevan, dan berorientasi pada pembentukan karakter peserta didik di tingkat sekolah dasar. Temuan ini memberikan implikasi penting bagi pengambil kebijakan, pendidik, dan peneliti dalam mengoptimalkan arah pengembangan pendidikan Islam pada masa mendatang.